Designing Android Based Software for Anthropometry, Hearing test, and Visual Test to Monitor Children Developmental Status - Zalni Rahmad Anakampun; Nabilah Nabilah; Cut Hasina Sonia; Masdar Maulana; Firman Parlindungan; Muhammad Reza Firdaus (J-Kesmas: Jurnal Fakultas Kesehatan Masyarakat (The Indonesian Journal of Public Health), 2021)
The World Health Organization (WHO) in 2018 reported that the prevalence for children under five with growth and development disorders was 28.7%, and Indonesia was included in the third country with the highest prevalence in the Southeast Asia region. As such, monitoring child growth and development is pivotal to determine necessary intervention and prevention. With technological advancement, monitoring child growth and development has become more accessible. The main objective of this paper is to explain the process of designing an Android software application for anthropometry, hearing test, and visual test to monitor children's developmental status. We employed to research and development methods, including need analysis, data collection, application design, user trial, and evaluation. The findings showed that the application could monitor growth and development in children from the age of zero to 72 months based on anthropometric testing related to auditory and visual stimulation in children. The application is useful in detecting the growth and development of children based on the results of the child's stimulation response. Based on the results of user trials by medical experts, parents, technological experts, it can be concluded that the software is applicable in monitoring the status of children's growth and development.